Comparing retrograde urethrography readings with intraoperative findings in urethral stricture - Kelkar, Tanvi Subhash; Joshi, Anil (International Journal of Research in Medical Sciences, 2019)
Background: Urethral strictures are relatively common in men with most patients acquiring the disease due to injury or infection. The present study was conducted to assess the accuracy of retrograde urethrography (RGU) in diagnosing urethral strictures in patients presenting with lower urinary tract symptoms. Methods: All male patients presenting with lower urinary tract symptoms and referred for retrograde urethrogram to the Department of Radiodiagnosis, Bharati Vidyapeeth Medical College and Hospital (Deemed to be University), Sangli from November 2018 till January 2019 were included. The parameters of RGU were compared with intra-operative findings as gold standard to calculate the operating characteristics of RGU. Results: The present study included 42 patients, mean age 54.9±11.2 years. Grade I urethral stricture was observed in 42.8% and 26% had grade II stricture. Bulbar stricture was the most common location. The common presenting complaints were increased frequency (50%) and dribbling micturition (40.4%). Approximately one tenth of all patients had a history of trauma. RGU was 100% sensitive and 66.7% specific in detecting strictures of less than 2 cm. Overall accuracy of RGU in detecting urethral strictures of less than 2 cm was 83.3%. Conclusions: RGU is a reliable means for establishing the diagnosis of a suspected urethral stricture and also provides accurate staging information with regard to stricture number, length, location, and coexistent urethral pathology.